The emission of secondary protons from reaction (p,xp) at an energy of 30 MeV in the nucleus of 103 Rh - Алиева, Г; Кабдрахимова, Г; Садыков, Б; Насурлла, М; Мукан, Ж; Усабаева, Г; Kucuk, Y; Жолдыбаев, Т (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
On the beam of accelerated protons of the U-150M cyclotron of the Institute of Nuclear Physics, double – differential reaction cross sections (p, xp) were measured on a 103 Rh nucleus at an energy E p =30 MeV. A self-sustaining foil with a thickness of 3 µm with an isotope content of 103 Rh ∼ 98% was used as targets. To identify the reaction products, a two-detector telescope was used, consisting of a transient thin silicon detector with a thickness of 100 µm and a total absorption detector (CsI (Tl) scintillator) 2.5 cm thick. The integral spectra were obtained from the double – differential cross sections with the subsequent determination of the total partial cross sections for the reactions (p, xp). The experimental results obtained were analyzed in the framework of a modified version of the exciton model of pre-equilibrium decay within the PRECO-2006 calculation code. It has been established that the cross sections for the reactions 103 Rh (p, xp) at a proton energy of 30 MeV are predominantly formed by the mechanism of pre-equilibrium decay.